School and students contest movement for talent reveal - S. . Shamets; M. . Knyazeva (Высшее образование в России)
The article describes the experience of Omsk State Technical University in organization of school and students contests for revealing the talented youth. The all-Russian, regional and university contests should be viewed as an effective instrument to enroll motivated entrants. These competitions also enable to organize the interaction between the university staff, school teaching personnel, and industrial enterprises and business organizations.